The secured credit premium and the issuance of secured debt - Benmelech, Efraim; Kumar, Nitish; Rajan, Raghuram (Journal of Financial Economics, 2022)
Credit spreads for secured debt are lower than for unsecured debt, especially when a firm's credit quality deteriorates, the economy slows, or average credit spreads widen. Yet investment-grade firms tend to be reluctant to issue secured debt at all times. In contrast, we find that for firms that are rated below investment grade, the likelihood of secured debt issuance increases as firm credit quality deteriorates, the economy slows, or average credit spreads widen. This differential pattern of issue behavior is consistent with highly rated firms seeing unencumbered collateral as a form of insurance, to be used only in extremis.